Left atrial cardiomyopathy and 10-year risk of Atrial Fibrillation. (3rd October 2022) - Uhe, T; Stegmann, T; Langhammer, R; Laufs, U; Dagres, N; Wachter, R
Abstract: Background: Left atrial cardiomyopathy (LACMP) is considered a precursor or prerequisite of incident atrial fibrillation (AF). Various definitions including humoral, ECG- and echocardiographic parameters have been proposed, but not been rigorously and comparatively investigated and the role of excessive supraventricular ectopic activity (ESVEA) is poorly studied. We aimed to analyse the ten-year risk to develop AF in patients with cardiovascular risk factors and to define the impact of LACMP, its components and ESVEA on AF risk. Methods: 148 patients free of AF at baseline were followed for 10 years. Baseline examination included medical history, physical examination, echocardiography, 12-lead-ECG and 7-day-Holter ECG. LACMP was defined as either left atrial enlargement (left atrial volume index (LAVI) >35 ml/m 2 ), P-terminal force in lead V1 (PTFV1) ≤ −4000 mscdotμV or elevated N-terminal pro-B-type natriuretic peptide (NT-proBNP) >250 pg/ml. Firstly, we analyzed the association of these parameters on AF-free survival in Kaplan-Meier plots. Secondly, we repeated this analysis for ESVEA (defined as either >720 premature atrial contractions (PAC) per day or at least one atrial run >20 beats per day). Finally, parameters significantly associated with AF-free survival were included in a multivariable analysis to identify those independently predictive for AF. Results: At baseline, eighty-nine patients fulfilled at least one criterion of LACMP while eight patients fulfilled all criteria. After ten years of follow-up, AF was newly detected in twelve patients (13.4%) with LACMP and two patients (3.4%) without LACMP (p=0.04). LAVI (p=0.005), ESVEA (p=0.016) and NT-proBNP (p=0.010) showed significant association with AF-free survival in univariate analysis while PTFV1 did not. In a combined Cox model of LACMP parameters, significant associations were found for log-transformed NT-proBNP (HR 3.56; 95% CI 1.33–5.31; p=0.04) and log-transformed PAC (HR 2.66; 95% CI 1.25–10.15; p=0.01) but not for LAVI and not for PTFV1. Conclusion: The risk for AF is higher in patients with evidence of left atrial cardiomyopathy. NT-proBNP and premature atrial contractions independently predict AF-free survival. The role of supraventricular ectopic activity is underestimated and requires further study. Funding Acknowledgement: Type of funding sources: None.